Reusing Semantics in Visual Editors: A Case for Reference Attribute Grammars - Fors, Niklas; Hedin, Görel (Electronic Communications of the EASST, 2013)
The semantic formalism reference attribute grammars (RAGs) allows graphs to be superimposed on abstract syntax trees. This paper investigates how RAGs can be used to model visual languages, with a case study of a control language that also has a textual syntax. The language contains blocks on which a total execution order is defined based on connections and layout information. One strength of RAGs is reusability, and we demonstrate this by reusing the definition of the execution order in the visual editor to provide semantic feedback to the user.